2017
DOI: 10.1016/j.neuron.2017.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Feedforward and Feedback Effects of Microstimulation in Visual Cortex Reveal Neural Mechanisms of Texture Segregation

Abstract: The visual cortex is hierarchically organized, with low-level areas coding for simple features and higher areas for complex ones. Feedforward and feedback connections propagate information between areas in opposite directions, but their functional roles are only partially understood. We used electrical microstimulation to perturb the propagation of neuronal activity between areas V1 and V4 in monkeys performing a texture-segregation task. In both areas, microstimulation locally caused a brief phase of excitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
81
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 61 publications
14
81
1
Order By: Relevance
“…It has been shown that variance in mean responses in V2 can be well predicted by variations in factors that determine the statistics necessary for the generation of natural textures, while variations in mean responses in V1 can be predicted by variations in statistics at the level of independent Gabor-like edge filters. Similarly, contextual modulation of V1 activity by top-down influences from V2 neurons was demonstrated when high-level inferences were made in artificial images (Klink et al, 2017;Lee and Nguyen, 2001). These results can be explained in terms of probabilistic inference in a hierarchical internal model of natural images, in which mean responses correspond to the most probable interpretation of the stimulus.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…It has been shown that variance in mean responses in V2 can be well predicted by variations in factors that determine the statistics necessary for the generation of natural textures, while variations in mean responses in V1 can be predicted by variations in statistics at the level of independent Gabor-like edge filters. Similarly, contextual modulation of V1 activity by top-down influences from V2 neurons was demonstrated when high-level inferences were made in artificial images (Klink et al, 2017;Lee and Nguyen, 2001). These results can be explained in terms of probabilistic inference in a hierarchical internal model of natural images, in which mean responses correspond to the most probable interpretation of the stimulus.…”
Section: Discussionmentioning
confidence: 66%
“…Investigations into the organization of feedback revealed that characteristic regularities present in the visual environment are reflected in the structure of both lateral (Kaschube, 2014;Löwel and Singer, 1992;McGuire et al, 1991;Schmidt et al, 1997;G. B. Smith et al, 2015) and top-down (Klink et al, 2017;Lee and Nguyen, 2001) interactions. These feedback interactions could thus establish dependencies between the responses of neurons whose receptive fields are sensitive to stimulus features that have high probability to co-occur in the visual environment and support perceptual grouping, such as the vicinity, continuity, collinearity, color and direction of motion of composing scene elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined above, while most studies have focused on waves during the stimulus onset response, travelling waves may be induced during sustained stimulation responses and during the brief increase of spiking activity at stimulus offset in the sensory cortex of awake, behaving animals, and these waves may not be time-locked to the stimulus. Bursts during the fast onset transient arise through feedforward input; however, during spontaneous and induced waves, these bursts can result from recurrent fluctuations or feedback connections 26,106 . Nevertheless, initial evidence indicates that induced waves travel over similar fibre networks as waves evoked during stimulus onset 66,77 .…”
Section: Network Mechanisms For Travelling Wavesmentioning
confidence: 99%
“…In contrast to FF-pathways, the neurobiology of the significantly more numerous FB pathways (Markov et al, 2014a) An early conceptualization of hierarchical processing in the cortex conceived of FF pathways driving target areas, and in contrast FB pathways merely exerting a modulatory influence (Klink et al, 2017), however, some researchers hold a more nuanced view (Bastos et al, 2012). Indeed, the simple dichotomy of the roles of FF and FB pathways is difficult to reconcile with the multiple physiological effects that are imputed to FB control.…”
Section: Diversity Of Fb Pathways and Their Function In Neural Computmentioning
confidence: 99%